ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN AKUNTANSI AKRUAL PADA PEMERINTAH PROVINSI RIAU (Studi Empiris Pada SKPD Provinsi Riau) - Kamemy, Laraswisesa; Savitri, Enni; ', Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
the research aims to analyze of influencing factors for implementing accrual accounting in government of Riau province. The data of this research is primer and started on July-August of 2016. Population of this research is department of SKPD Riau province. Samples of this research are one hundred twenty nine respondents with purposive sampling method. That data are analyzed by linear regression method and SPSS program version 19. The variables were examined are education level, training staff, the quality of information technology, additional supporting, experience, education background and size of SKPD. The results of this research showed education level has no effect to the implementing of accrual accounting with 0,622 significance, quality of technology has an effect to the implementing of accrual accounting with 0008 significance, training staff has an effect to the implementing of accrual accounting with 0,016 significance, additional supporting has an effect to the implementing of accrual accounting with 0,000 significance, education background has an effect to the implementing of accrual accounting with 0,001 significance., experience has an effect to the implementing of accrual accounting with 0,002 significance and size of SKPD has an effect to the implementing of accrual accounting with 0,537 significance The results of this research also showed that coefficient R square is 58,6%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study. All variables also have strong relation with variable dependents in this research.Keywords : Education,Training, Information, Supporting, Experience And Accrual Basic